The S.E.L.F. Approach: Systems and Experiential Learning Framework for Fieldwork and Capstone Education Development - Kasey Stepansky; Tina Lekas (Scholarworks @ WMU, 2020)
This article presents an evidence-based strategy to assist academic fieldwork coordinators and capstone coordinators with meeting the Accreditation Council for Occupational Therapy Education standards of experiential learning components in an entry-level doctoral occupational therapy curriculum. The S.E.L.F. approach core methods for pedagogical framework and manual development are based on systems theory and educational learning theories. To optimize fieldwork and capstone delivery, the recommended process should include organizational analysis, program development, manual writing, and implementation of practical learning experience. Objectives of the fieldwork and capstone experiences can effectively connect to the overall curriculum design while addressing integral credentialing standards through an evidence-based approach. The applied learning theories are pertinent for educators to objectively deliver beneficial experiential pedagogical outcomes for student professional growth. This article provides a logical fieldwork and capstone framework for pedagogical and manual development. The S.E.L.F. approach transforms learning to meet objectives of the occupational therapy program, students, and other potential audience stakeholders.